2017
DOI: 10.5005/jp-journals-10005-1451
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro Comparative Evaluation of Efficacy of Disinfecting Ability of Garlic Oil, Neem Oil, Clove Oil, and Tulsi Oil with autoclaving on Endodontic K Files tested against Enterococcus faecalis

Abstract: Aim To comparatively evaluate the efficacy of disinfecting ability of garlic oil, neem oil, clove oil, and tulsi oil with autoclaving on endodontic K files tested against Enterococcus faecalis.Materials and methods Fifty endodontic K files were exposed to the test micro-organism and checked for its disinfecting ability using three different methods.Result Garlic oil, clove oil, tulsi oil and autoclave showed considerable effectiveness against E. faecalis except neem oil.Conclusion Garlic oil, clove oil and tul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…The other arm of this study was garlic extract showed has antibacterial properties that have been proved against some microorganisms such as Pseudomonas , Klebsiella , Streptococcus mutans , and Porphyromonas gingivalis . Also, it was reported to be effective against E. faecalis similar to autoclave (Hugar et al, ). Garlic extract has better antibacterial properties when compared with calcium hydroxide (Eswar et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The other arm of this study was garlic extract showed has antibacterial properties that have been proved against some microorganisms such as Pseudomonas , Klebsiella , Streptococcus mutans , and Porphyromonas gingivalis . Also, it was reported to be effective against E. faecalis similar to autoclave (Hugar et al, ). Garlic extract has better antibacterial properties when compared with calcium hydroxide (Eswar et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The success of endodontic treatment depends upon effective disinfection and complete sealing of root canals. The most commonly found microorganism in failed/ infected root canals of both primary and permanent teeth is Enterococcus faecalis [65,66]. The following are some of the very few studies highlighting the efficacy of extracts of Neem as an efficient root canal disinfecting agent.…”
Section: As Endodontic Irrigantmentioning
confidence: 99%
“…Isolated microorganisms from the infected root canals have serious implications on oral and systemic health. [ 2 ] It has been observed from several studies that intracanal instrumentation does not remove all the microorganisms, but use of intracanal medicament helps in removal of remaining bacteria after cleaning and shaping. Enterococcus faecalis is the commonly found microorganism in failed/infected root canals of both primary and permanent teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Enterococcus faecalis is the commonly found microorganism in failed/infected root canals of both primary and permanent teeth. [ 1 2 3 ] This bacterium is most resistant and can survive even in 100–10,000 folds in starvation stage. [ 1 ] Various medicaments/irrigants are advised for disinfecting the root canal as well as for removal of microorganisms from inaccessible sites.…”
Section: Introductionmentioning
confidence: 99%